Dynamic Behavior and Management Strategy of Hybrid Wind/Fuel Cell System - Meharrar, A.; M. Hatti, M.; Tioursi, M.; Benmessaoud, T. (Journal of Technology Innovations in Renewable Energy, 2013)
hybrid generation system is considered as a solution for the uncontrolled energy production from such dispersed sources as wind generation. In this paper, modeling and control of wind/FC system is proposed. Dynamics models for the main system components, namely, wind energy conversion system (WECS), fuel cell, electrolyses, power electronic interfacing circuits, hydrogen storage tank and ultra-capacitor are developed. Also, a variable speed wind generation maximum power point tracking (MPPT) based on Adaptative Neuro-Fuzzy Inference system (ANFIS) is presented. Based on the dynamic component model, a simulation model for the proposed hybrid energy system has been developed using Matlab/Simulink and the power flows management strategy are proposed. The result shows that this system can tolerate the rapid changes in wind speed and/or power demand. This results shows also that, the overall power management strategy is effective and the power flows among the different energy sources and the load demand is balanced successfully.